Resolving Figurative Expressions During Reading: The Role of Familiarity, Transparency, and Context. Issue 7 (8th August 2020) - Carrol, Gareth; Littlemore, Jeannette
ABSTRACT: Native speakers understand familiar idioms (e.g., over the moon ) and conventional metaphors (e.g., describing time as a doctor) quickly and easily. In two eye-tracking studies we considered how native speakers are able to make sense of fundamentally unfamiliar figurative expressions. In Experiment 1 compared with literal paraphrases of the same meaning, known idioms had a clear advantage, unknown idioms showed a significant disadvantage, and conventional metaphors showed no difference between figurative and literal versions. In Experiment 2 readers saw known and unknown idioms (or paraphrases) in contexts that either supported the intended meaning or were neutral. Strength of context had minimal effect on reading patterns for either idiom type and had no effect when readers were asked to subsequently identify the meaning. Context may be helpful in terms of sense selection but not when new senses need to be generated, at which point aspects such as transparency become more important.